Heart rate recovery in normal and obese males with and without parental history of cardiovascular disease - Rahul; Narsingh Verma; Mayank Agarwal; Pravesh Vishwakarma; Arvind Kanchan; Pravesh Kumar (Journal of Family Medicine and Primary Care, 2020)
Background: Parental history of cardiovascular disease (CVD) and obesity is associated with delayed parasympathetic nervous system reactivation after exercise. Heart rate recovery (HRRe) after a minute of exercise is inversely related to cardiovascular events. Aim: To determine the effect of body mass index (BMI) and parental CVD history on HRRe in apparently healthy young Indian males. Method: The present cross-sectional experimental study involved 100 males, aged18–25 years. Subjects were divided into two equal groups based on the parental CVD history—(i) Parental CVD history present, and (ii) Parental CVD history absent. Each of these groups were further divided into two equal sub groups based on BMI—(a) BMI <23kg/m2, and (b) BMI ≥25 kg/m2. Participants exercised on the treadmill at variable speeds and grades to achieve their target HR (THR). THR was calculated by adding 60–90% HR-reserve (HRR) in their basal HR (BHR). HRR was calculated by subtracting maximal HR (MHR) from BHR. MHR was estimated by the formula: 208–0.7 × age. The HRRe was calculated by subtracting the immediate postexercise HR with the HR after a minute of rest postexercise. ANOVA with post-hoc Tukey was applied and a P value ≤0.05 was considered as statistically significant. Results: HRRe value was significantly lesser in subjects having a positive parental history of CVD than the subjects with no parental history of CVD, irrespective of BMI. Also, HRRe was inversely related to BMI. Conclusion: Not only obesity but also a family history of CVD impacts the recovery of HR after vigorous-intensity exercise.